Design of Information Service Model Based on Identification of Disciplinary Behavior of Class F Students at SMA N 4 Sumatera Barat (Sports Talent) - Tanjung, Sabrina; Nita, Rahma Wira; Chandra, Yasrial (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research was motivated by students who were late for class, students who missed school, students who did not comply with school rules, students who disturbed their friends while studying, and students who did not complete their assignments. The objectives of this research are: 1). Describe the disciplinary behavior of students at SMA Negeri 4 West Sumatra (sports talent). 2). The design of the information service model is based on identifying the disciplinary behavior of FASE F class students at SMAN West Sumatra (sports talent.) This research uses the Research and Development (R&D) type of research. The population of this study was FASE F class students with a total of 108 students. The number of samples in this study was 72 students. The sampling technique in this research used purp total sampling, and the instrument used was a questionnaire. Based on the results of this research, it is revealed that: 1) Describe the condition of student discipline with information services at SMAN 4 West Sumatra (sports talent) is in the very good category. 2) The program design that has been validated is in the